Isolasi Kitin Dari Limbah Cangkang Kepiting (Scylla SP) Dengan Variasi Pelarut Pada Proses Bleaching - Frederika Mawarni Adilasari Nduru; Drastinawati Drastinawati; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Crab shell is a waste that reach 50-60% of total weight, with chitin content of 20-30%. Chitin is biopolymer commercially used in biochemistry, medicine, textile, agriculture and others. The main aim of this research is to compare the level of lightness and whiteness of chitin produced in the bleaching process with organic and inorganic solvents. The research was started by reducing the size of the crab shell into a powder. Chitin was isolated by deproteination process using 3.5% NaOH and demineralization process using HCl 1N, followed by bleaching process with organic solvents variation of methanol; ethanol; acetone; ethanol:acetone (1:1), inorganic solvents of NaOCl 4%; Ca(OCl)2 3%; H2O2 3%, and the combination of acetone fallowed by NaOCl 0.315%. The result obtained is chitin without bleaching process with a yield of 24.44%, water content of 4%, and ash content of 1.75%. The IR spectrum analyzed before and after bleaching process showed relativity similiar absorption and were not affected by the solvent used in bleaching process. The color of chitin was analyzed using colorimeter. The result is the use of acetone fallowed by NaOCl 0.315% yileding chitin with 100% lighteness, 99.95% whiteness and categorized as white.Keywords: bleaching, crab shell, chitin, lightness, and whiteness.